Policy Evaluation of Malang City Government: A Study on the Stagnation of “Desaku Menanti” Program in Mask Village - Holqi, Fikri Gali Fernando; Kumalasari, Luluk Dwi (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
Tourism operations in Kampung Topeng, or Mask Village, Malang City, Indonesia, stagnated in the post-COVID era before closing permanently. This study examines the public policy of tourism development in Kampung Topeng by the Malang City Government through the Desaku Menanti program from the Ministry of Social Affairs of the Republic of Indonesia. This study uses a qualitative approach with a case study. Data was collected from observations, interviews, documentation, and document studies. This study found that the development of regional tourism in Malang City has been listed in the Mid-Term Regional Development Plan, which contains two priority aspects, the development of urban tourist destinations and the improvement of community welfare. The problems in the tourism sector can be attributed to the top-down government policies, low community participation, the succession of the Head of Social Service in Malang City, and the disintegration between the Social Service, Tourism Office, and Civil Service Police. This disintegration was caused by relocation that failed to empower. The findings emphasize the importance of considering community aspirations in creating sustainable and participatory policies.